2021
DOI: 10.3390/cancers13102387
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Selected Head and Neck Cancer Prognostic Markers from the Pathology Atlas in an Oral Tongue Cancer Cohort

Abstract: The Pathology Atlas is an open-access database that reports the prognostic value of protein-coding transcripts in 17 cancers, including head and neck cancer. However, cancers of the various head and neck anatomical sites are specific biological entities. Thus, the aim of the present study was to validate promising prognostic markers for head and neck cancer reported in the Pathology Atlas in oral tongue squamous cell carcinoma (OTSCC). We selected three promising markers from the Pathology Atlas (CALML5, CD59,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…CALML5, known as calmodulin-like 5, is a skin-specific calcium-binding protein that is closely related to keratinocyte differentiation (Mehul 11 et al, 2001). A previous study showed that the high expression of CALML5 was strongly associated with better survival in patients with head and neck squamous cell carcinomas (Wirsing et al, 2021). Misawa et al (Misawa et al, 2020) reported that the methylation of CALML5, led to its downregulation, and this showed a correlation with HPV-associated oropharyngeal cancer.…”
Section: Discussionmentioning
confidence: 94%
“…CALML5, known as calmodulin-like 5, is a skin-specific calcium-binding protein that is closely related to keratinocyte differentiation (Mehul 11 et al, 2001). A previous study showed that the high expression of CALML5 was strongly associated with better survival in patients with head and neck squamous cell carcinomas (Wirsing et al, 2021). Misawa et al (Misawa et al, 2020) reported that the methylation of CALML5, led to its downregulation, and this showed a correlation with HPV-associated oropharyngeal cancer.…”
Section: Discussionmentioning
confidence: 94%
“…CALML5, known as calmodulin-like 5, is a skin-specific calcium-binding protein that is closely related to keratinocyte differentiation ( Mehul et al, 2001 ). A previous study showed that the high expression of CALML5 was strongly associated with better survival in patients with head and neck squamous cell carcinomas ( Wirsing et al, 2021 ). Misawa et al ( Misawa et al, 2020 ) reported that the methylation of CALML5, led to its downregulation, and this showed a correlation with HPV-associated oropharyngeal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…CALML5 and FCGBP are on the list of favorable prognostic genes for HNSCC (available at ; , respectively). Furthermore, CALML5 was validated by the HNSCC cohort at mRNA and protein levels [ 44 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…CALML5 expression could be a protective mechanism for patient survival. Furthermore, CALML5 was validated by the HNSCC cohort at mRNA and protein levels [ 44 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation